Isolation and Characterization of Campylobacter jejuni subsp. jejuni from Macaroni Penguins (Eudyptes chrysolophus) in the Subantarctic Region - Broman, T. (American Society for Microbiology, 2000)
On Bird Island, South Georgia, albatrosses (n = 140), penguins (n = 100), and fur seals (n = 206) were sampled for Campylobacter jejuni. C. jejuni subsp. jejuni was recovered from three macaroni penguins (Eudyptes chrysolophus). These isolates, the first reported for the subantarctic region, showed low genetic diversity and high similarity to Northern Hemisphere C. jejuni isolates, possibly suggesting recent introduction to the area.